series of clinical observations of the treatment of patients with atrophic nonunion and defects of the clavicle midshaft managed with free fibular autografting, the Ilizarov mini-fixator and an intramedullary wire - Sergey N. Kolchin; Denis S. Mokhovikov; Tatiana A. Malkova (Гений oртопедии, 2025)
Introduction Atrophic nonunion and defects is a rare complication of clavicle fractures. Therefore questions arise when choosing the optimal method of their treatment. Purpose We aimed to retrospectively assess the effectiveness of treating atrophic clavicle midshaft nonunion and defects with a free fibular autologous graft fixed with the Ilizarov mini-fixator in combination with an intrameduallary wire. Materials and methods A retrospective study of 14 patients (11 females, 3 males) in the mean age of 34.1 ± 2.8 years with atrophic nonunion and defects of the clavicle was carried out. Eleven patients had post-traumatic nonunion after failures of its surgical treatment including seven cases of multiple surgeries, and three cases were congenital nonunion. Pain in the clavicle area was the main complaint in 13 patients. Five had minor restrictions in the shoulder joint function, and two had a pronounced adduction contracture of the shoulder joint. Surgical treatment included debridement, resection of the ends of the fragments to the paprika sign, defect plasty with a free autologous fibular graft followed by combined fixation with an intramedullary wire and the Ilizarov mini-fixator. Supportive compression of 1 mm every two weeks was produced at the junction of the fragments in order to stimulate repair. The mini-fixator was removed after radiographic confirmation of a continuous union of the graft with the fragments. Results and discussion The post-resection defect averaged 3.1 ± 0.2 cm. Union was achieved in 11 cases. The average period in the mini-fixator was 159.9 ± 11.9 days. In all cases, after dismantling the device, the range of motion in the shoulder joint retained preoperative parameters. The complications were one graft migration, soft-tissue inflammation and deep infection (two cases). Soft-tissue inflammation was treated with antibiotics while deep infection required prompt debridement. Long-term results were followed in 13 patients. There were no problems with the donor site in the long term. The Ilizarov mini-fixator assisted by an intramedullary wire provides stable fixation and allows compression at the junction of bone fragments with a fibular autograft to stimulate bone formation and union in clavicle midshaft nonunion and defects. Conclusion The combination of three technical components (autologous grafting, Ilizarov mini-fixator, intramedullary wire) yields positive results in the management of large post-resection defects of the clavicle midshaft. Upon graft consolidation, the clavicle acquires a near-to-normal radiographic bone structure.